In vivo optoacoustic imaging of endothelin receptor expression and treatment response in the hypoxic tumor microenvironment. - Höltke, Carsten; Mallik, Moushami; Stölting, Miriam; Hoffmann, Emily; Geyer, Christiane; Erapaneedi, Raghu; Kiefer, Friedemann; Helfen, Anne (European Journal of Nuclear Medicine & Molecular Imaging, 2026)
Purpose: A hypoxic tumor microenvironment promotes cancer progression, with endothelin-A receptor (ETAR) signaling playing a key role in tumor neoangiogenesis and macrophage infiltration. We hypothesize that multispectral optoacoustic tomography (MSOT) using an ETAR-specific probe could provide improved insights into the hypoxic characteristics of the tumor microenvironment (TME), either alone or in combination with endogenous markers, and that alterations in ETAR expression may correlate with increased tumor oxygenation serving as an early indicator of response to anti-angiogenic or immune-modulating therapy. Methods: A fluorescent ETAR probe was applied for in vivo MSOT evaluation of ETAR expression in hypoxic murine breast cancer. Optoacoustic signal intensity (SI) of deoxygenated and oxygenated hemoglobin served as additive intrinsic readouts. Furthermore, therapeutic interventions utilizing Bevacizumab, Clodronate and Sorafenib were evaluated with regard to effects on ETAR expression and hemoglobin oxygen saturation. Imaging results were validated ex vivo via immunohistochemistry. Results: Exposure of 4T1 murine breast cancer cells to hypoxic conditions led to upregulation of ETAR in vitro. In vivo, tumor growth correlated with increased ETAR probe signal intensity in 4T1 tumors. All therapeutic interventions significantly reduced ETAR SI following treatment. Anti-angiogenic therapies also increased tumor oxygen saturation, indicating therapy-induced re-oxygenation. Conclusion: ETAR expression in hypoxic tumor regions can be visualized non-invasively by MSOT using an exogenously administered targeted probe. Combining ETAR-targeted imaging with intrinsic hemoglobin readouts enables assessment of reoxygenation and immune cell modulation in response to therapy. Thus, ETAR has potential as an in vivo imaging biomarker for early therapy response in experimental breast cancer studies.